Maternal and Infant Morbidity and Mortality in Relation to Delivery Mode in a Large U.S. Health Care Claims Database in 2019 and 2020 - Doherty, Brett T.; Lynch, Stephanie; Naavaal, Aneesh; Li, Chrissie; Cole, Kimberly; MacPhee, Leslie; Banning, Leslie; Sharma, Anup; Grabner, Michael; Stanek, Eric; Inglis, Tiffany (American Journal of Perinatology, 2024)
This study aimed to provide contemporary data on maternal and infant outcomes after delivery to better understand risks of cesarean section (CS).Data for deliveries in 2019 and 2020 were obtained from a large U.S. commercial health care claims database. Maternal morbidity measures included 20 severe maternal morbidity (SMM) outcomes and seven additional obstetric and mental health outcomes. Infant morbidity measures included eight outcomes related to respiratory health, digestive health, atopic dermatitis, and birth trauma. Outcome prevalence was ascertained at 42 days (maternal only) and 360 days after delivery. Logistic regression was used to estimate the odds ratio (OR) and 95% confidence interval (CI) for prevalence adjusted for risk factors for delivery mode and each outcome. Analyses were conducted for 2019 and 2020 to assess the influence of the coronavirus disease 2019 pandemic.A total of 436,991 deliveries were identified (145,061 CS; 291,930 vaginal). The prevalence of SMM was 3.3% at 42 days and 4.1% at 360 days. The covariate-adjusted odds of SMM were higher among CS than vaginal deliveries at 42 days (OR: 2.0, 95% CI: 1.9, 2.1) and 360 days (OR: 1.7, 95% CI: 1.7, 1.8). There were 226,983 infants available for analysis of outcomes at 360 days. Most adverse infant outcomes were more prevalent at 360 days among CS than vaginal deliveries, and the covariate-adjusted odds of any adverse infant outcome at 360 days were higher among CS than vaginal deliveries (OR: 1.2; 95% CI: 1.1, 1.3). Respiratory morbidity was most affected by delivery mode. Maternal and infant mortality up to 360 days was rare. Similar trends were observed in the 2019 and 2020 cohorts.This observational study, performed using recent data obtained from a large U.S. commercial claims database, provides contemporary evidence of risks to mothers and infants of CS relative to vaginal delivery.
Keywords: delivery mode; cesarean section; SMM; mortality; maternal; infant; COVID-19; real-world data